Effects of Echinochloa crusgalli and Cyperus difformis on yield and eco-economic thresholds of rice. (20th June 2020) - Tian, Zhihui; Shen, Guohui; Yuan, Guohui; Song, Kun; Lu, Junyao; Da, Liangjun
Abstract: Echinochloa crusgalli and Cyperus difformis are malignant weeds in rice fields and a significant threat to rice production. To determine the interaction effects of E. crusgalli and C. difformis on the yield, eco-economic thresholds and control period of rice, field experiments were performed for two consecutive years (2017–2018) to study rice yield under different densities and coexistence periods of E. crusgalli and C. difformis. The results showed that the number of spikes, filled grains per panicle, 1000-grain weight, and rice yield decreased with increasing density and a prolonged coexistence period of the two weeds. From the perspective of the density gradient, under the condition of mixed of E. crusgalli and C. difformis and rice during the whole growth period, weeds must be controlled when the mixed density of weeds reaches 2.77 plants/m2. Regarding the duration of the coexistence period, under the density conditions set in the experiment, weed control must be carried out within 20 days after rice planting. Based on the analysis of ecoeconomic thresholds and the control period of mixed weeds, weed control should not involve the blind use of herbicides and can play a guiding role in reducing the number and quantity of herbicides used, saving weeding costs and protecting the ecological environment of farmland. Highlights: The eco-economic threshold based on weed mixed density was analyzed. The control period based on the coexistence period of mixed weeds and crops was addressed. Positive guide was given on avoiding the blind use of herbicides and protecting the ecological environment of farmlands.